Inappropriate behaviors and hypersexuality in individuals with dementia: An overview of a neglected issue. Issue 6 (4th August 2016) - Torrisi, Michele; Cacciola, Alberto; Marra, Angela; De Luca, Rosaria; Bramanti, Placido; Calabrò, Rocco Salvatore
Abstract : Behavioral and psychological symptoms of dementia are very common in patients affected by dementia, and are associated with high rates of institutionalization. Behavioral and psychological symptoms of dementia consist of aggressive behavior, delusions, hallucinations, depression, apathy, wandering, stereotyped and inappropriate sexual behavior. Interestingly, the latter has been reported to be relatively uncommon, but causing immense distress to patients and their caregivers. The genesis of inappropriate behavior is considered a combination of neurological, psychological and social factors. Although assessment is mainly carried out by clinical observation and interviews with caregivers, the most appropriate management of behavioral and psychological symptoms of dementia, including hypersexuality, is a combination of pharmacological and non‐pharmacological interventions, according to specific symptoms, degree of cognitive dysfunction and subtype of dementia. The present narrative review will mainly focus on aggressiveness, disinhibition, aberrant motor, and sexually inappropriate behavior diagnostic work‐up and treatment, in an attempt to provide both the patients and their caregivers with useful information to better manage these symptoms and improve their quality of life. Space is particularly dedicated to inappropriate sexual behavior, which is still considered a neglected issue.Geriatr Gerontol Int 2017; 17: 865–874.